A simple method for simultaneous determination of acetaldehyde, acetone, methanol, and ethanol in the atmosphere and natural waters - Giubbina, Fernanda F.; Scaramboni, Caroline; De Martinis, Bruno S.; Godoy-Silva, Daniely [UNESP]; Nogueira, Raquel F. P. [UNESP]; Campos, M. Lucia A. M. (Royal Soc Chemistry, 2017)
Although there has been a dramatic increase in the use of ethanol fuel in several countries, there is a great lack of data related to the abundance of this alcohol and associated species in the atmosphere and in natural waters. This data paucity is mainly due to the fact that their low concentrations in the environment pose a considerable analytical challenge. This work presents a simple and low-cost method to simultaneously determine acetaldehyde, acetone, methanol, and ethanol at environmentally relevant concentrations in the atmosphere and in a variety of natural waters. The target compounds present in the aqueous phase were analyzed by conventional headspace gas chromatography with flame ionization detection. External pretreatment of the aqueous samples was not necessary, providing savings in the cost and time of analysis. Satisfactory recoveries (96-108%) and good agreement with a high performance liquid chromatography method for determination of acetaldehyde, methanol, and ethanol endorsed the accuracy of the proposed method. Precision was better than 15% for the lowest concentration quality control sample tested, and was better than 8% for higher concentrations. Linearity (r) was better than 0.99 and the limits of detection for acetaldehyde, acetone, methanol, and ethanol were 0.20, 0.21, 1.45, and 0.41 mu mol L-1, respectively. The sensitivity of the method enabled the measurement of the target compounds in atmospheric samples collected in Brazil ranging from 3.6 to 20.6 ppbv. Rainwater, freshwater, and coastal seawater sample concentrations ranged from <0.20 to 0.85 mu mol L-1 for acetaldehyde, from 0.21 to 0.98 mu mol L-1 for acetone, from 6.20 to 15.7 mu mol L-1 for methanol, and from 0.41 to 7.61 mu mol L-1 for ethanol.